1999
DOI: 10.1097/00005650-199902000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Location of Care

Abstract: Many patients prefer to undergo surgery locally even when travel to a regional center would result in lower operative mortality risk. Therefore, policy makers should consider patient preferences when assessing the expected value of regionalizing major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
238
2
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(251 citation statements)
references
References 22 publications
7
238
2
4
Order By: Relevance
“…Regionalization and selective referral could result inevitably in adverse outcomes by limiting patient choice and access to care, increasing unreasonable transfer and travel burdens and reducing the availability of surgical services in many locations, particularly in rural areas remote from the high-volume centers. (94,95) The volume-based referral policy also may have unintended consequences for patients at lower-volume hospitals who have conditions that are not on the selective referral list. (79) Third, patients might not benefit equally from regionalization or selective referrals.…”
Section: The Volume-based Policies In Risky Surgeries and Transplantmentioning
confidence: 99%
“…Regionalization and selective referral could result inevitably in adverse outcomes by limiting patient choice and access to care, increasing unreasonable transfer and travel burdens and reducing the availability of surgical services in many locations, particularly in rural areas remote from the high-volume centers. (94,95) The volume-based referral policy also may have unintended consequences for patients at lower-volume hospitals who have conditions that are not on the selective referral list. (79) Third, patients might not benefit equally from regionalization or selective referrals.…”
Section: The Volume-based Policies In Risky Surgeries and Transplantmentioning
confidence: 99%
“…[36][37][38][39] Referral to highvolume centers is often met with resistance by both patients and providers, leads to disparities in which minorities and the underinsured are less likely to receive referral to a high-volume center, and is problematic in many regions that lack high-volume facilities. [36][37][38][39] Furthermore, for lower-risk patients undergoing high-risk surgery, the benefits of volume-based referral are questionable; it appears that the greatest benefits are derived in the highest-risk patient population undergoing the highest risk surgeries. 40 Given these difficulties, some authors have suggested that regionalization should primarily be encouraged for high morbidity procedures with strong volume-outcome relationships like pancreatectomy and esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,14 However, it has been shown that patients prefer to see physicians closer to home, despite a possibly higher mortality. 23 Primary care physicians may also wish to refer patients to specialists based on qualities such as appointment timeliness and communication. 24 There is a possibility that rural patients are underserved by urban centres despite idealistic intentions.…”
Section: Discussionmentioning
confidence: 99%